Recently Registered Midazolam Doses for Preterm Neonates Do Not Lead to Equal Exposure: A Population Pharmacokinetic Model. (15th May 2019) - Völler, Swantje; Flint, Robert B.; Beggah, Fouzi; Reiss, Irwin; Andriessen, Peter; Zimmermann, Luc J.I.; van den Anker, John N.; Liem, Kian D.; Koch, Birgit C.P.; de Wildt, Saskia; Knibbe, Catherijne A.J.; Simons, Sinno H.P.
Abstract: Although midazolam is a frequently used sedative in neonatal intensive care units, its use in preterm neonates has been off‐label. Recently, a new dosing advice for midazolam for sedation on intensive care units has been included in the label (0.03 mg/[kg·h] for preterm neonates <32 weeks and 0.06 mg/[kg·h] for neonates >32 weeks). Concentration‐time data of a prospective multicenter study (29 patients, median gestational age 26.7 [range 24.0‐31.1 weeks]) were combined with previously published data (26 patients, median gestational age 28.1 [range 26.3‐33.6 weeks]), and a population pharmacokinetic model describing the maturation of midazolam pharmacokinetics was developed in NONMEM 7.3. Clearance was 73.7 mL/h for a neonate weighing 1.1 kg and changed nonlinearly with body weight (exponent 1.69). Volume of distribution increased linearly with body weight and was 1.03 L for a neonate weighing 1.1 kg. Simulations of the newly registered dosing show considerable differences in steady‐state concentrations in preterm neonates. To reach similar steady‐state concentrations of 400 µg/mL (±100 µg/mL), a dose of 0.03 mg/(kg·h) is adequate for neonates ≥1 kg and ≤2 kg but would have to be reduced to 0.02 mg/(kg·h) (−33%) in neonates <1 kg and increased to 0.04 mg/(kg·h) (+33%) in neonates weighing >2 kg and ≤2.5 kg. The impact of the observed differences in exposure is difficult to assess because no target concentrations have yet been defined for midazolam, but the current analysis shows that one should be cautious in giving dosage advice based on historical data with a lack of reliable pharmacokinetic and effect data.